PERAN PERPUSTAKAAN GAMPONG LAMDINGIN DALAM MENINGKATKAN MINAT BACA SANTRI TPA (TAMAN PENDIDIKAN AL-QUR’AN) - Sri Wahyuni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Since the implementation of Regional Autonomy, the term village can be referred to by other names, for example in West Sumatra Province it is known as